(untitled) (American Journal of Technology and Applied Sciences, 2024)
Artificial Intelligence (AI) is revolutionizing the healthcare industry, particularly in the early detection of diseases. By analyzing large datasets and identifying patterns that may not be immediately visible to human clinicians, AI offers the potential to enhance diagnostic accuracy, reduce costs, and improve patient outcomes. This article delves into the innovations AI brings to early disease detection, including machine learning algorithms, medical imaging, and wearable health technology. It also addresses the significant challenges associated with integrating AI into healthcare systems, such as data privacy concerns, regulatory hurdles, and the need for robust infrastructure. The article concludes by emphasizing the importance of collaboration between technologists, healthcare providers, and policymakers to fully realize the potential of AI in early disease detection.